Відновлення інтересу до магнітоелектричного ефекту у нанофероїках - Glinchuk, M. D.; Khist, V. V. (Publishing house "Academperiodika", 2018)
Recent theoretical studies of the influence of the magnetoelectric effect on the physical properties of nanosized ferroics and multiferroics have been reviewed. Special attention is focused on the description of piezomagnetic, piezoelectric, and linear magnetoelectric effects near the ferroid surface in the framework of the Landau–Ginzburg–Devonshire phenomenological theory, where they are considered to be a result of the spontaneous surface-induced symmetry reduction. Therefore, nanosized particles and thin films can manifest pronounced piezomagnetic, piezoelectric, and magnetoelectric properties, which are absent for the corresponding bulk materials. In particular, the giant magnetoelectric effect induced in nanowires by the surface tension is possible. A considerable influence of size effects and external fields on the magnetoelectric coupling coefficients and the dielectric, magnetic, and magnetoelectric susceptibilities in nanoferroics is analyzed. Particular attention is paid to the influence of a misfit deformation on the magnetoelectric coupling in thin ferroic films and their phase diagrams, including the appearance of new phases absent in the bulk material. In the framework of the Landau–Ginzburg–Devonshire theory, the linear magnetoelectric and flexomagnetoelectric effects induced in nanoferroics by the flexomagnetic coupling are considered, and a significant influence of the flexomagnetic effect on the nanoferroic susceptibility is marked. The manifestations of size effects in the polarization and magnetoelectric properties of semiellipsoidal bismuth ferrite nanoparticles are discussed.